Similar phonemes create interference in the serial recall task. - Roodenrys, Steven; Miller, Leonie M.; Guitard, Dominic; Neath, Ian (Memory, 2025)
The mechanisms underlying forgetting have been central to theorising about verbal short-term and working memory, and the importance of interference as opposed to decay continues to be vigorously debated. Here, we present two experiments to evaluate the nature and locus of phonological interference as a source of forgetting in serial recall. In these experiments, we replicate studies showing that repetition of phonemes across items impairs recall of the later list item, even with visual presentation and typed recall. In addition, we manipulate the degree of phonemic overlap between a target word and preceding words in the list, and demonstrate that consonants that are only similar, as opposed to identical, to each other can interfere with the recall of other list items. Taken together, the experiments suggest that the primary factor driving phonological interference is the similarity of the articulatory features of the phonemes.